THE EFFECT OF SOME ECOLOGICAL FACTORS ON THE SURVIVAL OF SOME DERMATOPHYTES - B. Nasr Esfahani1; M.Moghaddami (Tehran University of Medical Sciences, 1991)
The effect of some ecological factors on the survival of Trichophyton violaceum T.mentagrophytes and M. gypseum was studied. Three types of sterile soil, weakly alkaline (pH =7.9).neutral (pH=7.1) and acid (pH =5.6), and two conditions of wet and dry environments at different temperatures (-8, +8, + 1s, +3O, i~445 were examined. After 4, 10,15,30,60, and 90 days the survival of these fungi were studied. Survival was best in weakly alkaline soil, dry or wet conditions, at temperature below 30c although M. gypseum could resist 44c in a dry condition for more than 90 days. The present study showed that the type of soil is the determinative factor for survival and distribution of these fungi.